2000
DOI: 10.1054/bjoc.1999.1095
|View full text |Cite
|
Sign up to set email alerts
|

Mitoxantrone and ametantrone induce interstrand cross-links in DNA of tumour cells

Abstract: SummaryWe show here that mitoxantrone and ametantrone induce interstrand DNA cross-links in HeLa S 3 cells. These cross-links were observed only in cellular system suggesting that metabolism of the drugs is a necessary step leading to DNA cross-linking. Biologically inactive analogue of mitoxantrone, compound NSC 321458, did not induce cross-links in DNA of tumour cells which suggests that DNA crosslinking is associated with the cytotoxic and anti-tumour activity of these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…However, in addition to this mechanism it has also been demonstrated that the oxidation products of mitoxantrone (catalyzed by horseradish peroxidase) form a covalent complex with DNA in vitro (5), and similar drug-DNA adducts were subsequently also detected when mitoxantrone was oxidized in vitro by the human enzyme myeloperoxidase (6). The detection of drug-DNA adducts in mitoxantrone-treated promyelocytic HL-60 cells (which contain myeloperoxidase) (7) and in other tumor cells (8) subsequently provided direct support for the notion that mitoxantrone-DNA adducts may contribute to the mechanism of action of mitoxantrone.…”
mentioning
confidence: 99%
“…However, in addition to this mechanism it has also been demonstrated that the oxidation products of mitoxantrone (catalyzed by horseradish peroxidase) form a covalent complex with DNA in vitro (5), and similar drug-DNA adducts were subsequently also detected when mitoxantrone was oxidized in vitro by the human enzyme myeloperoxidase (6). The detection of drug-DNA adducts in mitoxantrone-treated promyelocytic HL-60 cells (which contain myeloperoxidase) (7) and in other tumor cells (8) subsequently provided direct support for the notion that mitoxantrone-DNA adducts may contribute to the mechanism of action of mitoxantrone.…”
mentioning
confidence: 99%
“…33 Reports indicated that MTX produce DNA cross-links and DNA replication defects in tumour cells, once DNA damage occurs, ATM pathway for HR repair is activated. 34 the maintenance of genomic integrity and cellular viability. 35 It is demonstrated that DNA-damaging drugs (including MTX) can trigger an ATM-dependent DNA damage response, leading to increased cytokine secretion and resistance to chemotherapy-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…19 chemotherapeutic drug for many types of cancer, we chose HeLa cells as it has specifically been shown to induce inter-strand cross-links in DNA of tumorigenic HeLa cells [71]. We quantified the cytotoxicity using the WST-1 reagent in 96-well assays.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%